2020
DOI: 10.1371/journal.pone.0228938
|View full text |Cite
|
Sign up to set email alerts
|

Microvasculopathy and soft tissue calcification in mice are governed by fetuin-A, magnesium and pyrophosphate

Abstract: Calcifications can disrupt organ function in the cardiovascular system and the kidney, and are particularly common in patients with chronic kidney disease (CKD). Fetuin-A deficient mice maintained against the genetic background DBA/2 exhibit particularly severe soft tissue calcifications, while fetuin-A deficient C57BL/6 mice remain healthy. We employed molecular genetic analysis to identify risk factors of calcification in fetuin-A deficient mice. We sought to identify pharmaceutical therapeutic targets that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 71 publications
(89 reference statements)
2
31
0
3
Order By: Relevance
“…In line with other studies using different animal models to target the PPi/Pi ratio by either TNAP inhibition or PPi supplementation, we found no differences in circulating PPi levels between the different study groups [ 19 , 32 , 49 , 50 ]. It is worth noting that the PPi plasma values reflect the whole-body PPi metabolism.…”
Section: Discussionsupporting
confidence: 91%
“…In line with other studies using different animal models to target the PPi/Pi ratio by either TNAP inhibition or PPi supplementation, we found no differences in circulating PPi levels between the different study groups [ 19 , 32 , 49 , 50 ]. It is worth noting that the PPi plasma values reflect the whole-body PPi metabolism.…”
Section: Discussionsupporting
confidence: 91%
“…D2,Ahsg-/-mice are certainly one of the most calcification-susceptible mouse strains known [29]. Concurrent with this work we established that the calcification phenotype of D2,Ahsg-/-mice is governed by combined deficiency of fetuin-A, pyrophosphate and magnesium, thus at once affecting three potent extracellular regulators of mineralization [30]. Unsurprisingly, this prominent calcification phenotype is associated with bone abnormalities [31], decreased breeding performance, organ damage, and increased mortality.…”
Section: Introductionsupporting
confidence: 54%
“…The full penetrance and severe expression of the calcification phenotype renders D2,Ahsg-/-mice ideal for studying mechanisms and therapeutic approaches for calcification diseases. A concurrent study from our laboratory has shown that the severe soft tissue calcification in the mice is governed by fetuin-A, pyrophosphate and magnesium, and can in fact be prevented by prophylactic supplementation of each one of these major systemic inhibitors of calcification [30]. The aim of this present study was to analyze the early events leading to soft tissue calcification in these mice.…”
Section: Discussionmentioning
confidence: 94%
“… 46 Exogenous fetuin-A supplementation inhibits the development of calcified thrombi in fetuin-A–deficient mice, confirming its relevance to vasculopathy. 44 Expectedly, serum Ca 2+ , PO 4 3 − , low fetuin-A, and high CPP levels all associate with the development of vascular pathology. 47 49 …”
Section: Calcium and Phosphate Homeostasis And The Generation Of Cppsmentioning
confidence: 96%
“…MGP- and GRP-deficient mice develop medial arterial calcifications 34 , 42 , 43 and may prematurely die from blood vessel rupture. 34 Fetuin-A–deficient mice develop numerous calcified thrombi in the microvasculature 44 , 45 and intimal arterial calcifications on atherosclerosis-prone genetic backgrounds. 46 Exogenous fetuin-A supplementation inhibits the development of calcified thrombi in fetuin-A–deficient mice, confirming its relevance to vasculopathy.…”
Section: Calcium and Phosphate Homeostasis And The Generation Of Cppsmentioning
confidence: 99%